Preventing and managing behavioural problems in regular classrooms: Perceived preparedness of future teachers in Switzerland and Quebec - Bonvin, Patrick; Gaudreau, Nancy (Swiss Journal of Educational Research, 2018)
In the context of school inclusion, classroom and behaviour management represent an important challenge. Our study describes Swiss and Quebec future teachers’ perceptions of their capacity to apply efficient prevention and behaviour management strategies. Results yield differences according to participants’ nationality, and partially reproduce previous research results showing that teachers perceive their education programs as lacking in classroom management courses, and do not feel skilled in this area. Finally, they attribute their current capacity levels to their practical experiences rather than to their theoretical training.